Degradation of methyl orange using ultrasonic irradiation: enhanced with adsorption using newspaper - Mazlan, Sadri (2010)
Nowadays, the type of dye being released by textile industry is named by azo dyes. There are many researchers has used the technique of ultrasonic irradiation to degrade the dyes pollutant. In this study, the ultrasonic irradiation simultaneous with adsorption method using newspaper will apply to degrade methyl orange solution. The ultrasonic bath cleaner (50 – 60kHz) was used to degrade methyl orange with and without the presence of low cost adsorbent which is newspaper waste at initial concentrations 10 mg/l t0 100 mg/l, initial pH 1 to pH 12, also temperature at 300C to 800C and contact time from 20min to 120 min.. The newspaper used was cut into small size in range 4mm to 5mm. The absorbance value of Methyl orange (MO) solution before and after the degradation process was analyzed using UV-Vis Spectrophotometer. Maximum of 11% degradation achieved on the effect of initial concentration study. For initial pH effect, maximum of 24 % degradation was achieved at pH 1.Also maximum 11% degradation achieved for the study on the effect of temperature. Degradation percentage was increased in increasing of time. Maximum 12% degradation was achieved at up to 120 min contact time. By using ultrasonic bath cleaner, we can conclude that degradation can be achieved using ultrasonic irradiation method simultaneous with adsorption method. The percentage degradation was increased with the increased of temperature and time. However percentage degradation was decreased with increased of initial concentration. The pH value brought some pattern into degradation percentage. The ability of newspaper sorbent in order to degrade methyl orange solution in the presence of ultrasonic irradiation indicated that such sorbent could be employed as low cost alternatives to commercialize like as activated carbon in wastewater treatment for the removal of color and dyes.